Importance of Duration, Duty-Cycling and Thresholds for the Implementation of Ultraviolet C in Marine Biofouling Control - Whitworth, Paul; Aldred, Nick; Reynolds, Kevin J.; Plummer, Joseph; Duke, Phillip W.; Clare, Anthony S. (Frontiers in Marine Science, 2022)
The introduction of a surface into the marine environment begins a process known as biofouling, which increases the weight and hydrodynamic drag of the fouled structure. This process is detrimental to maritime vessels and costs the industry ∼$150B in fuel and maintenance spending annually. Preventing the settlement of fouling organisms mitigates these issues and limits the spread of non-indigenous species (NIS). This is primarily achieved via antifouling paints. Ultraviolet light is a sterilization method used in water purification, food storage packaging, and within medical fields. Ultraviolet C (UV-C) radiation interacts with DNA to prevent growth, proliferation, and survival of bacteria, and biofilm formation. Recent progress in microelectronics technology has advanced the range of commercially available light-emitting diodes (LEDs) to include the UV wavelengths, and the reduced size and cost has allowed their integration into previously inaccessible locales. This study builds on recent progress in integrating UV-C LEDs into UV-lucent silicone tiles for fouling control. The operational cycle needed to prevent growth of Navicula incerta cells was determined. Constant irradiance at a peak of 5.77 μW/cm2 resulted in a significant reduction in diatoms within 2 h, and a 2 log and 3 log reduction after 48 h and 5 days, respectively. Duty cycling (pulsing) in all variations from 50 to 2.5%, indicated significant reductions in cell densities, and the lowest cycle could effectively reduce biofouling growth and increase the longevity of the LEDs for up to 45.6 years. Irradiance and exposure were altered over a set duration and indicated a restriction in growth between 0.01–0.82 J/cm2 and an increased mortality at irradiances > 2.65 J/cm2, suggesting an effective antifouling threshold between these dosages. The effective dosage for 1 log reduction in fouling was estimated to be 25 J/cm2 but varied according to irradiance delivery method. Effective dosage for a 1 log reduction between experimental methods was variable indicating that UV treatment of N. incerta departed from the Bunsen-Roscoe reciprocity law expectancy. The variation in densities at similar dosages could be explained with further investigation of DNA repair mechanisms. In conclusion, UV-B/C use was effective at all irradiances, including as low as 0.01 J/cm2, and holds considerable promise for marine biofouling control.